Assessment of Bangladesh Public Procurement System - World Bank (World Bank, Washington, DC, 2020)
Bangladesh has enjoyed relatively high and stable growth over the last two decades,accompanied by rapid poverty reduction. Gross domestic product (GDP) growth averagedclose to 6 percent annually since 2000 and, according to official estimates, accelerated toover 8 percent in FY19. The poverty rate dropped from 44.2 percent in 1991 to 14.8 percentin 2016. With per capita gross national income (Atlas method) at $1,954 in 2019, Bangladeshhas moved into lower middle-income country status since 2015. The Government of Bangladesh (GOB)’s Vision 2021 aims to propel the country into middle-income status and further reduce poverty. The most recent five-year plan (FYP16-20) focusses on productive employment for the growing labor force and a substantial increase in investment. Other key elements of the plan are to ensure good governance and pursue for an environmentally sustainable and socially inclusive development process. The key objectives of the assessment were to: (i) establish a shared understanding of thecurrent state of Bangladesh public procurement system amongst all stakeholders; (ii) identifythe strengths and weaknesses of the overall public procurement system and formulateappropriate mitigation measures for the identified gaps; and (iii) develop action plan forfuture system development in achieving a modern and harmonized procurement system withparticular reference to enhanced e-GP, contract management, sustainable procurement, andcitizen engagement.